Proteins in solution and at interfaces methods and applications in biotechnology and materials science - Ruso, Juan M. (Ruso Beiras, Juan Manuel); Piñeiro, Ángel, 1973- (Wiley series on surface and interfacial chemistry, 2013)
"Proteins in solution and at interfaces are increasingly used in exciting new applications, from biomimetic materials to nanoparticle patterning. This book surveys the state-of-the-art in the field, providing scientists in diverse areas with a comprehensive and modern analysis of the techniques used in protein characterization, as well as insight into the most important applications. Topics include protein and protein aggregate structure; computational and experimental techniques for the study of protein structure, aggregation, and adsorption; proteins in non-standard conditions; and biotechnological applications"--